Tearing up the rulebook: Feminist mothering in Kay Mellor's In the Club. Issue 3 (1st October 2019) - Rodgers, Julie
There has been a notable proliferation of maternal 'truth-telling' texts on British television and on social media in recent years which serve as a backlash of sorts to more normative and prescribed narratives of motherhood. Kay Mellor's In the Club (2014–present) is an example of one such televisual text. As this article demonstrates, In the Club can be positioned as a subversive and feminist representation of the maternal with its emphasis on mothering as messy and chaotic and, most importantly, pluralistic in experience. In addition to close analysis of the series itself, the article discusses the importance of mother-centric television and the need for more nuanced visions of the maternal. However, the article also argues antithetically that while televisual series like In the Club do much to deconstruct the patriarchal 'masterscript' of motherhood, there are many instances when they inadvertently end up reinforcing the norms.